The Role of Attitude in Mediating Gen Z’s Intention in Use of Digital Sharia Banking - Wartoyo, Wartoyo; Sudrajat, Anton; Wiyani, Silva; Subagiyo, Rokhmat; Haqqiquddin Rokhmatulloh, Muhammad Raisa; Fauzan (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: Dynamic technological developments make a significant contribution to human life. In the banking world, one of the technological developments that has changed the way of transactions is the emergence of payment instruments known as digital banking. Therefore, this research aims to determine the effect of convenience and usefulness on interest in using digital banking with attitude as an intervention variable for Gen Z in Cirebon Regency. Method: The research uses a quantitative approach with the type of non-parametric data. The sampling technique used random sampling with a number of samples are 100 respondents. The data analysis technique uses Structural Equation Modeling (SEM) with the tool is SEM-PLS. Result: The results of the first test show that the Convenience and Usefulness has a significant effect on attitudes to use digital banking. Likewise in the second test show the Convenience, Benefit and Attitude has a significant effect on interest in using digital banking. Whereas the result of mediating test show that the Attitudes have a significant influence as an intervening variable between ease and interest in using digital banking, also has a significant effect as an intervening variable between ease and interest in using digital banking. Conclusion & Suggestion: The findings of this study show that the main factor that attracts Gen Z in using Digital Banking is the ease of use factor, therefore banks must always pay attention to the user interface (UI) and user experience (UX) of their applications. The intuitive design and easy transaction process will be very attractive to Gen Z. In addition to convenience, the benefits offered also need to be more concrete and relevant to the needs of Gen Z. Knowing that attitudes have a very important role in influencing interest, digital banks can build campaigns that focus not only on features and benefits, but also on forming a positive perception of digital banking.